A comprehensive look at the return predictability of variance risk premia. Issue 4 (5th October 2017) - Byun, Suk Joon; Frijns, Bart; Roh, Tai‐Yong
Abstract : The discrepancy between in‐sample and out‐of‐sample predictability of common predictors for asset returns has been widely discussed in the literature. We examine the out‐of‐sample predictability and its economic significance of Variance risk premium (VRP), which recently has shown empirical success in predicting asset returns in‐sample. Extensive analysis indicates strong out‐of‐sample predictability of the VRP for U.S. stock index, currencies, credit index, and equity portfolios. However, we do not find any evidence for predictability of bond and commodity markets. We demonstrate economic significance by providing profitable market timing strategies exploiting the out‐of‐sample forecasting power of the VRP in a real time setting.